Comparison of How Arabic and English Foreign Language Learners Compliment and Respond to Praises - Kamsinah, Kamsinah; Sain, Yuliyanah; Aliah, Nurazizah; Natsir, Nurasia (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2022)
Researching the speech acts performed between Arabic and English speakers is one of the popular trends in pragmatic research. However, the majority of previous studies have only obtained data from native Arabic and English speakers, or Arabic natives who are learning English as a foreign language. This study intends to fill the research gap of comparing the speech acts of giving praise and responding to praise made by students who are studying both English and Arabic as their foreign languages. This descriptive study used two instruments, namely a discourse completion task questionnaire consisting of twelve scenarios and an interview, involving 70 English learners and 70 Arabic learners from UIN Alauddin Makassar which is the only university in Indonesia that offers the unique Foreign Language Intensification Development (PIBA) program. Results have determined that the dominant praise strategies of Arabic learners are awe and congratulating, while English learners tend to use surprise and congratulating strategies. Both language learners dominantly use the strategies of giving appreciation and reassigning praises as their praise response strategies. This study concluded that Arabic foreign language learners tend to have a small repertoire of praise and praise response strategies, while English foreign language learners’ arsenal of strategies is much more diverse.